The psychology of food choice - Raats, Monique; Shepherd, R. [ (Richard)] (Frontiers in nutritional science, 2006)
One of the central problems in nutrition is the difficulty of getting people to change their dietary behaviors so as to bring about an improvement in health. This book tells about the influence on human food choice. It covers topics such as: models of fod choice; biological and learning influences on food choice; and, societal influences